Comparison of pyruvate kinase variants from human breast tumor and normal breast - Yilmaz, S; Ozan, ST; Ozercan, IH (Wiley, 2005)
[Abstract Not Available]
30th Congress of the Federation-of-European-Biochemical-Societies (FEBS)/9th IUBMB Conference -- JUL 02-07, 2005 -- Budapest, HUNGARY